Diabetes self‐management education: Looking for better choices. Issue 8 (August 2017) - Hawks, Matthew; Moss, David
Abstract : N/A: Lorig K, Ritter PL, Turner RM, English K, Laurent DD, Greenberg J. Benefits of diabetes selfmanagement for health plan members: a 6‐month translation study. J Med Internet Res . 2016; 18(6):e164.